Akomodasi Komunikasi dalam Komunikasi Antarbudaya Santri Jawa di Pondok Pesantren Al Hikam Assalafiyyah, Bantarkawung - Reza Abineri; Fany Anggun Abadi; Viky Rizki Imanullah; Dede Suryadi (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
At Al Hikam Assalafiyyah Islamic Boarding School, Bantarkawung intercultural communication occurs almost daily. Ethnic differences among students bring variations to their communication behavior. For example, Javanese and Sundanese students enrich their interactions with their respective cultural quirks, which can sometimes lead to problems and even arguments. For example, when two individuals from Java and Sunda discuss papaya, the Javanese call it